2012
DOI: 10.1145/2096140.2096147
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing e-government maturity in transition economies and developing countries

Abstract: This study examines the influences of relevant environmental factors on E-government (E-gov) maturity in transition economies and developing countries (TEDC). Countries from Eastern Europe, Sub-Saharan Africa, Latin American and South Asia were selected for the study. Prior research has investigated E-gov growth, development, and diffusion across both the developed and developing worlds. While such a focus is useful for comparative analyses at a global level, it is however argued that more useful information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 60 publications
(130 reference statements)
2
43
1
Order By: Relevance
“…D'Agostino's et al (2011), Park (2007), and all agree that static websites that are typical of small-sized local government agencies are ineffective in delivering the eGovernment services expected by citizens in the digital age. In fact, the rate of adoption of ICTs to support citizen empowerment in the form of e-Government was assessed as "fair" to "low" in the extant [33,34] .…”
Section: A Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…D'Agostino's et al (2011), Park (2007), and all agree that static websites that are typical of small-sized local government agencies are ineffective in delivering the eGovernment services expected by citizens in the digital age. In fact, the rate of adoption of ICTs to support citizen empowerment in the form of e-Government was assessed as "fair" to "low" in the extant [33,34] .…”
Section: A Implicationsmentioning
confidence: 99%
“…The implication of this current research may indicate that one of the primary factors that was found to increase the digital divide gap, lack of high-speed broadband Internet, did not seem to be a factor in the cities and census designated places explored in the study. community Public Library should be the leader in broadband high-speed Internet access for the location they serve [34] , [35] . Research question two (Q2 ) identified that the greatest citizen empowerment opportunity identified was the use of social media.…”
Section: A Implicationsmentioning
confidence: 99%
“…Previous research has also utilized this combination as a measure of eGov maturity, e.g. Ifinedo (2011) and Srivastava and Teo (2007).…”
Section: Egovernment Maturitymentioning
confidence: 99%
“…Of course, these findings did not eliminate the importance of technological advancements and infrastructure for the eGov success (Singh et al, 2007;Azad et al, 2010;Relly and Sabharwal, 2009;Siau and Long, 2004). Ifinedo (2011) also showed that the greater the level of technological innovative capacity of a country, the higher its eGov maturity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation